Pharmacognostic Characteristics, Chemistry, Biological Activity And Toxicity of Lolium Species - Al-Sa'idy, Hussein Ali Hussein; Hamid, Hussein Kamil (Asian Journal of Pharmaceutical Research and Development, 2022)
Around seven species of the genous lolium poisonous grasses belonging to the family Poaceae are mutually grown in corps field over the world. In Iraq the prennel ryegrass is locally called “rewatta”.The toxicity of these gasses are related to three chemically distinct alkaloids groups; the aminopyrrolizidine; lolines, indole-diterpenes (ergots, loliterms, and paxillines) as well as peramine alkaloids mostly concentrated in their seeds although indole-diterpene alkaloids loliterm B and paxilline biosynthesis requires endophytes symbiosis. The level of loline alkaloids enhances in both late summer-autumn of the year as well as in the infected dry plant materials up to 10 fold. However, paxilline and ergovaline are believed to be the precursor of the most toxic lolium species alkaloids, loliterm B, although, indole-diterpene alkaloids paxillines, loliterms and ergovaline are the actual indicators of Lolium species. In this review we summarize chemical characteristics, biological and toxicological influences as well as their interrelation of the plant of lolium genus. Central as well as peripheral biological/toxicological manifestations are summarized for both loline and indole-diterpene alkaloids. Finally, toxic influences of lolium alkaloids are function of their biological influences mostly exhibited via resembling molecular mechansims centrally as well as peripherallyare concluded.